Genetic variation of the D-loop region of the Kinh ethnic group from the northern, central, and southern Vietnam - La, Duy; Dinh, Thao; Thuy Duong, Nguyen (Academia Journal of Biology, 2025)
The displacement-loop (D-loop) region is the 1122 bp sequence of the mitochondrial DNA (mtDNA) that plays an important role in mtDNA replication and transcription. This region is also a hotspot for mutations, making it a good candidate for genetic diversity studies, especially when combined with other unique characteristics of the mitochondria. The Kinh, which accounts for approximately 90% of the Vietnamese population, has been extensively used as a representative of the Vietnamese population. In this study, we sampled and sequenced the mtDNA of 31 Kinh individuals from Central Vietnam and 33 Kinh individuals from Southern Vietnam. In combination with 50 Northern Kinh mtDNA sequences from a previous study, the present study analyzed the diversity of the Kinh across Vietnam through the D-loop region. After aligning to the reference mtDNA sequence RSRS (Reconstructed Sapiens Reference Sequence), 134 unique variants were found in the D-loop region, including 34 variants found in all three populations, 25 variants found in two populations, and 75 variants unique to one Kinh population. Haplogroup calling using Haplogrep3 identified 60 haplogroups, with 23 out of 60 being absent in the Northern Kinh population. Interestingly, despite the genetic diversity of the Kinh, four haplogroups were found in all three populations (F1a1a, F1a2, B5a, M7b1a1+(16192T)). The pairwise genetic distance analysis showed that the Northern Kinh is distinguishable from the Central Kinh while the other pairing experienced the opposite trend. By sampling the Kinh group in three different regions, our results provided the basis for further genetic diversity analysis of the Kinh across Vietnam.